Jenna Phillips: capstone - Phillips, Jenna, artist (Colorado State University. Libraries, 2014)
The artist's statement: The more I observe the world around me, the more infatuated I am with the extraordinary similarities that all life forms seem to share, and drawing these connections is a process that is very important to me. I find the grotesque and disgusting parts of human anatomy uniquely beautiful and I am compelled to compare them to aspects of nature that are more universally seen as beautiful and interesting. These natural patterns are gifts hidden within our own bodies as well as the animal and plant biology surrounding us. As an artist I am interested in the idea that many biological phenomena in our world both look and function a like. The human brain has a wonderful tendency to pick up visual information and put it into a context that makes sense to them. Likewise our world works in a series of systems known as the systems theory. System theory is the transdisciplinary study of the abstract organization of phenomena, independent of their substance, type, or spatial or temporal scale of existence. These drawings were a study of comparing universally recognized plant and animal bits and comparing them to parts of our own bodies that may be recognizable to some but not necessarily identifiable. My paper and color choice was made to focus the viewer on the patterns and not necessarily the form. I enjoy the task of creating new anatomies and morphing different creatures into new forms that are neither dead nor alive but merely existing. These unifying factors have become less representative of the anatomy it comes from but rather works with other anatomies to show the elaborate decorations naturally given to us and our surrounding world.
Colorado State University Art Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.